WOCAT SLM Technology: “Small-Scale Seed Cleaning Unit [Tunisia]” - Rudiger, Udo; Frija, Aymen; Idoudi, Zied; Zaiem, Anis; Dhehibi, Boubaker; Rekik, Mourad; Louahdi, Nasreddine (The Global Database on Sustainable Land Management (SLM) of WOCAT, 2023)
The mobile seed cleaning machine improves the livelihoods of smallholder farmers in Tunisia by significantly enhancing seed quality, increasing crop production, reducing workload and costs, and promoting local value chains and social cohesion. In Tunisia and Algeria, the agricultural system is characterized by low levels of mechanization, particularly among small and medium-sized farmers who cannot afford expensive imported machines. As a result, a substantial amount of manual labor is required to carry out various agricultural operations, such as seed cleaning, which is traditionally done by women and children. While seed production is often handled by large suppliers, this does not always meet the demand. Therefore, many smallholder farmers in Tunisia prefer to use their own seeds, despite the time-consuming manual cleaning process and the risk of lower quality. To address these issues, the International Center for Agricultural Research in Dry Areas (ICARDA) collaborated with national partners to develop a mobile seed cleaning machine for small-scale farmers. The prototype, designed and tested with input from a local manufacturer, is suitable for primary field crops, such as wheat, barley, vetch, and faba beans, commonly grown in Tunisia. The machine sorts out damaged or undersized seeds and removes rocks or pebbles, while treating the remaining seeds to eliminate contamination or weeds, ensuring quality and longer shelf life. The introduction of the mobile seed cleaning machine has several advantages, including a reduction in the workload for women and children, improved crop production and quality, increased land productivity, reduced dependence on imported seeds and machinery, and the promotion of local value chains and social cohesion through cooperative ownership and shared utilization of the machines.